Neurodevelopmental Outcomes after Pediatric Cardiac ECMO Support - Chrysostomou, Constantinos; Maul, Timothy; Morell, Victor O.; Callahan, Patrick M.; Nguyen, Khoa; Lichtenstein, Steven; Coate, Emma G.; Wearden, Peter (Frontiers in Pediatrics, 2013)
Purpose: To characterize the neurodevelopmental outcomes and identify factors associated with poor outcomes in pediatric patients undergoing cardiac extracorporeal membrane oxygenation (ECMO). Methods: Five year retrospective review, including demographics, cardiac lesion and surgical complexity, reason for ECMO, ECMO complications, and neurodevelopmental status at discharge and latest follow-up. Neurodevelopmental status was determined through the Pediatric Overall Performance Category and Pediatric Cerebral Performance Category scales. Results: Overall ECMO survival was 73% at hospital discharge and 66% a t the latest follow-up. Most patients underwent CPR (43%), and the majority (53%) had a significant disease complexity (Aristotle=4). Complications occurred in 42% of the ECMO runs, of which 12% were intracranial injuries. At hospital discharge, 75% of patients had normal to mild disability, improving to 81% at 2 years follow-up. At hospital discharge, moderate to severe disability was associated with CPR, plasma exchange or intracranial insults. After discharge, 23% showed improvement in neurologic status and 4% showed deterioration. Cerebral infarction was the only parameter associated with deterioration at the later follow-up stage. Conclusions: ECMO was successfully used in children with cardiac disease with 73% and 66% short and long-term survival respectively. Majority of the survivors had normal to mild neurodevelopmental disability and a significant portion showed neurologic improvement by the latest follow-up. Nevertheless, despite the grossly favorable outcomes standardized comprehensive neuropsychological testing is of paramount importance in all these patients.